PENERAPAN PENGENDALIAN INTERNAL PERSEDIAAN UNTUK MENCEGAH TINDAKAN KECURANGAN UMKM KOPI CIRENGOT - Andhika Ligar Hardika; Supriyanto Ilyas; Paulus Sugianto Yusuf; Rini Susiani; Syafdinal Syafdinal (ITB AAS Indonesia Surakarta, 2024)
This study aims to find out how fraudulent acts can be detected and evaluated using internal control measures in the inventory cycle. This research was conducted using a descriptive method. Data collection techniques were carried out using a combination of observation, interviews and literature studies. Data processing is done by analyzing the results of interviews related to the area and comparing them with the results of observations. The results of the study show that internal control is very effective in preventing and detecting fraud in the inventory cycle at MSMEs Cirengot Coffee. The risk of fraud can be handled and prevented adequately. Implementation of controls such as increasing physical supervision, separation of functions and authority, strict and written policies on the company can be a solution to prevent fraud in MSMEs Cirengot Coffee.